Pengaruh Model Pembelajaran Berbasis Masalah (Problem-Based Learning) Terhadap Kemandirian Belajar Siswa Pada Mata Pelajaran Akidah Akhlak (Studi Eksperimen Di Kelas VIII MTs Muhammadiyah Tarogong Garut) - Salamudin, Ceceng; Utami, Sri Rahayu (MASAGI : Jurnal Pendidikan Agama Islam, 2023)
The self-directed learning of students in the Akidah Akhlak subject at MTs Muhammadiyah Tarogong Garut remains a challenge in the educational process. Some students exhibit low self-confidence, lack responsibility, and are overly dependent on others during learning activities. The Problem-Based Learning (PBL) model is an instructional approach that engages students in solving problems through scientific method stages.   The objectives of this research are to describe: (1) the level of self-directed learning in students concerning the Akidah Akhlak subject; (2) the implementation of the Problem-Based Learning model in the Akidah Akhlak subject for Grade VIII students at MTs Muhammadiyah Tarogong Garut; and (3) the influence of the Problem-Based Learning model on students' self-directed learning in the Akidah Akhlak subject for Grade VIII students at MTs Muhammadiyah Tarogong Garut.   The research employed an experimental method. Data collection techniques included observation, questionnaires, and document analysis. The data were processed using statistical analysis. The study's findings revealed that the average pre-test scores were 52.70 for the experimental group and 52.35 for the control group. After the treatment with the Problem-Based Learning model, the post-test average for the experimental group increased to 62.00, while the control group, which did not use the PBL model, had an average post-test score of 54.87. The T-test results indicated \( T_{calculated} \) > \( T_{table} \), specifically \( -6.59 \) or \( 6.59 > 2.00 \).   Therefore, it can be concluded that the Problem-Based Learning model significantly influences the self-directed learning of students in the Akidah Akhlak subject for Grade VIII students at MTs Muhammadiyah Tarogong Garut. Keywords : Problem-Based Learning Model, Student Self-Directed Learning, Akidah Akhlak Subject